Measurement of e+ e− → DD̄ cross sections at the ψ(3770) resonance*Supported by National Key Basic Research Program of China (2015CB856700), National Natural Science Foundation of China (NSFC) (11235011, 11335008, 11425524, 11625523, 11635010), the Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, the CAS Center for Excellence in Particle Physics (CCEPP), Joint Large-Scale Scientific Facility Funds of the NSFC and CAS (U1332201, U1532257, U1532258), CAS Key Research Program of Frontier Sciences (QYZDJ-SSW-SLH003, QYZDJ-SSW-SLH040), 100 Talents Program of CAS, National 1000 Talents Program of China, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology, German Research Foundation DFG under Contracts Nos. Collaborative Research Center CRC 1044, FOR 2359, Istituto Nazionale di Fisica Nucleare, Italy, Koninklijke Nederlandse Akademie van Wetenschappen (KNAW) (530-4CDP03), Ministry of Development of Turkey (DPT2006K-120470), National Science and Technology fund, The Swedish Research Council, U. S. Department of Energy (DEFG02-05ER41374, DE-SC-0010118, DE-SC-0010504, DE-SC-0012069), University of Groningen (RuG) and the Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (July 2018) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ahmed, S.; Albrecht, M.; Alekseev, M.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, Y. 羽; Bakina, O.; Baldini Ferroli, R.; Ban 班, Y. 勇; et al.
Abstract: We report new measurements of the cross sections for the production of DD̄ final states at the ψ(3770) resonance. Our data sample consists of an integrated luminosity of 2.93 fb −1 of e + e − annihilation data produced by the BEPCII collider and collected and analyzed with the BESIII detector. We exclusively reconstruct three D 0 and six D + hadronic decay modes and use the ratio of the yield of fully reconstructed DD̄ events ("double tags") to the yield of all reconstructed D or D̄ mesons ("single tags") to determine the number of D 0 D̄ 0 and D + D − events, benefiting from the cancellation of many systematic uncertainties. Combining these yields with an independent determination of the integrated luminosity of the data sample, we find the cross sections to be σ (e + e − → D 0 D̄ 0 ) nb and σ (e + e − → D + D − ) = (2.830 ± 0.011 ± 0.026) nb, where the uncertainties are statistical and systematic, respectively.